Arts Across the Disciplines: Using the Voices of the Oppressed and Vulnerable to Inspire Analytical Thinking in the Human Services Curricula - Ardith A. Peters; Irene S. McClatchey (Park University, 2017)
This paper addresses how professors in a Social Work and Human Services Program in the Southeastern United States include voices of the oppressed and vulnerable through art forms to develop analytical thinking to prepare human service practitioners. This pedagogical practice is based on Gardner's discussion of Multiple Intelligences. The authors also offer examples, discuss outcome measures for each, cite student responses, and provide considerations for inclusion in course work. This article is focused on human services curricula, such as social work, psychology, clinical psychology, and counseling, but the concepts can be used in a variety of human services professional education settings.